Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12913-021-07298-z
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Chinese version of the partners at care transitions measure

Abstract: Background The Partners at Care Transitions Measure (PACT-M) is a measure that assesses the quality and safety of care during the transition from hospital to home from the patient’s perspective. The aim of this study was to examine the psychometric properties of the Chinese version of the PACT-M in Mainland China. Methods This was a cross-sectional study. A convenience sample of patients was recruited from three tertiary hospitals affiliated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The primary outcomes include hospitalization-related indicators, such as readmission or emergency room visits, and respiratory-related indicators, such as exacerbation history, mMRC [18], CAT [19], and Test of the Adherence to Inhalers [20]. The secondary outcomes include the Hospital Anxiety and Depression Scale [21], self-efficacy [22], and Transition Care Quality Assessment [23].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcomes include hospitalization-related indicators, such as readmission or emergency room visits, and respiratory-related indicators, such as exacerbation history, mMRC [18], CAT [19], and Test of the Adherence to Inhalers [20]. The secondary outcomes include the Hospital Anxiety and Depression Scale [21], self-efficacy [22], and Transition Care Quality Assessment [23].…”
Section: Discussionmentioning
confidence: 99%
“…We used a cross-sectional study design and the Chinese version of PACT-M which can assess the quality of transitional care from the patient’s perspective to evaluate the quality of transitional care [ 16 ]. We investigated three affiliated hospitals of Zhengzhou University in Henan Province and two tertiary hospitals in Shanxi Province.…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach’s alpha values for PACT-M 1 and PACT-M 2 were 0.802 and 0.741, and the test–retest reliability values were 0.885 and 0.837. The results of both the exploratory factor analysis (EFA) and the confirmatory factor analysis (CFA) showed that both parts of the PACT contained two dimensions, the item content validity index and scale content validity index values of PACT-M 1 and PACT-M 2 were 1.0 [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Under the guidance of the above-mentioned policies, the total amount of medical and health service resources in China has continued to grow and the level of medical technology and medical quality has been continuously improved. Currently, a health and medical service network has been formed that covers both urban and rural areas [ 8 ]. Most elderly patients with chronic diseases can receive transitional care after returning home from the hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation